The tablet has landed. - Ochs, Susie; Aguilera, Ray.; Curthoys, Paul.
After years of speculation, Apple's tablet--the iPad--is almost here. We've spent hours using several iPads, and they're the closest thing to a notebook that Apple will ever make. Our no-holds-barred analysis will help you understand that iPads are good for--and whether you should buy one.
Keywords: Kindle (Electronic book reader); iPhone (Smartphone); Electronic book readers; Tablet computers; iPad; iPad CPU; iBooks; e-Reader.; iPhone Software